Terapia ocupacional e reabilitação profissional : práticas e concepções de terapeutas ocupacionais no Instituto Nacional do Seguro Social (INSS) - Bregalda, Marilia Meyer (Universidade Federal de São Carlos, 2012)
Alongside with the establishment of the Brazilian Social Security, the Professional Rehabilitation of the National Institute of Social Security (INSS) has been created. It aims to provide its beneficiaries, partially or totally incapacitated for work, the indicated means to reenter the labor market and the context in which they live. This study intended to understand, identify and comprehend, from the perspective of occupational therapists, practices and conceptions that have been delineated by the profession in the area of Professional Rehabilitation at INSS, in the state of Sao Paulo. Based on a survey and an analysis of bibliographical and documental material on the theme in general and at the Institute in particular, the empirical research made use of a questionnaire applied with 40 of the 43 occupational therapists who act in the state. In-depth interviews were conducted with 6 of these participants. Also an interview with another occupational therapist, who works at INSS since 1980, was conducted in order to collect background data about the Professional Rehabilitation as well as the insertion of occupational therapy at the Institute. The resulting data of the questionnaires provided a general prospect of conceptions and practices of occupational therapists in the studied field and were related to those collected in the interviews. This allowed for the deepening of the themes, providing opportunities for further reflection and discussion about them. The main findings allow us to state: occupational therapists are amidst the construction of a new professional identity at INSS; most of them deemed to have taken specific actions of occupational therapy at the Institute and point out the job analysis and the evaluation of compatibility of the proposed new functions for the insured workers in this specificity. The therapist-patient relationship was indicated like fundamental to their practice. Overall, they identify series of factors that would implicate an evaluation more negative than positive about their performance at the Institute, caused principally by structural questions of the Program of Professional Rehabilitation, what is independent of them. However, they still keep the belief in the improvement of this structure, claiming for the need to increase the possibilities offered by even greater participation and accountability by companies, the construction of joint work with other sectors of society and government, as well as for the redesigning and expansion of the legislation that deals with professional rehabilitation in Brazil.
Keywords: Terapia ocupacional; Reabilitação profissional; Trabalho; Instituto Nacional do Seguro Social (Brasil); Previdência social; Professional rehabilitation; Occupational therapy; National Institute of Social Security; Work; Social security; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL